The effect of culture filtrates of the saprophytic fungi isolated from peas and field peas roots and nodules on the growth of Rhizobium leguminosarum - Helena Furgał-Węgrzycka (Acta Mycologica, 2014)
In the work the effect of culture filtrates of biotic series of 34 species of saprophytic fungi isolated from roots and root nodules of peas and field peas on the growth of Rhizobium leguminosarum was determined. The results obtained proved that the growth of Rhizobium leguminosarum was inhibited by culture filtrates of saprophytic fungi: Aspergillus niger, A.flavus, Cephalosporium roseum, Cylindrocarpon radicicola, Fusarium oxysporum, F. solani, Glocladium roseum, Penicillium notatum, P. janthinellum, Trichoderma lignorum, and T. viride.